Development of a Distributor Disc for Mineral Fertilizers With Variable Application Rate - V. S. Teterin; N. S. Panferov; S. A. Pekhnov (Сельскохозяйственные машины и технологии, 2022)
Most of the cultivated fields in Russia are acknowledged to have irregular contours, therefore mineral fertilizers are applied irrationally at the field boundaries. To eliminate this problem, the manufacturers of solid mineral fertilizer spreaders offer several technological solutions: in most cases, the application area is limited by changing the granule flight path. (Research purpose) To develop a distributor disc for a variable application area to use in mineral fertilizer spreaders equipped with variable rate application systems. (Materials and methods) The trajectory for applying mineral fertilizer granules was estimated depending on the bend angle of the distributor disk blade. We designed 3D disk models with a variable blade bend angle from 0 to 25 degrees, which were uploaded into the RealFlow program for the subsequent simulation of solid mineral fertilizer distribution. (Results and discussion) The coordinates were obtained for mineral fertilizer granules that dropped from the disk and landed on the surface. We built graphs of the mineral fertilizer distribution on the field surface. It was found out that changing the bend angle of the distributor disc blade within a 20-degree range makes it possible to vary the granule flight path within 10 meters of width and 8 meters of length, respectively. We developed a design of a mineral fertilizer distributor disk with an adjustable application rate. (Conclusions) A disk design was proposed for a smooth change in the blade bend angle within up to 25 degrees, which will allow the use of this system in conjunction with automated rate application systems, improve the distribution accuracy of solid mineral fertilizers and ameliorants in the boundary, edge and wedge-shaped sections of fields.